Taking stock : An Update on Vietnam’s Recent Economic Developments - World Bank (World Bank, Hanoi, 2018)
The report examines economic developments in Vietnam in 2018, including its strong trade performance, increased FDI inflows, and public debt stabilization, among others. It also includes a special section on the government’s efforts to reduce trade costs and enhance competitiveness. A four-pillar integrated program on trade facilitation and logistics, is outlined. It includes : 1) Promoting trade facilitation by simplifying customs and specialized management regulations; (2) Enhancing efficiency of trade-related infrastructure and the quality of connectivity; (3) Building a competitive logistics service sector; and, (4) Strengthening interagency coordination and partnership with the private sector. It is intended to reduce non-tariff costs, thereby further boosting export-led growth, improving the business environment, and enhancing competitiveness.